Lectotypification of the name Genista michelii (Fabaceae) - Wagensommer, Robert P. (Phytotaxa, 2017)
As part of an ongoing study on the names of vascular plants described from Puglia (south-eastern Italy) (e.g., Wagensommer & Galasso 2016, Wagensommer et al. 2016), a nomenclatural investigation on the name Genista michelii Spach (1844: 259), which appears to be yet untypified, is presented here. This study is carried out within the initiative “Italian Loci Classici Census” (Domina et al. 2012, Passalacqua et al. 2014, Peruzzi et al. 2015), aimed at providing data on the original material of plants described from Italy and neighbouring areas.